(untitled) (World Bulletin of Public Health, 2023)
Hemostasis system studied of 54 pregnant complicated women obstetric history and fetal poisoning syndrome. The hemostatic system in pregnant women with thrombophilia is characterized by acivaton of platelet hemostasis by increasing the number of platelets, hypercogulability, as evidenced by an increase in the amount of soluble complexes fibrin monomer thrombinemia witnesses.